PERKEMBANGAN DAN PERILAKU PENEMPELAN LARVA GASTROPODA ABALON TROPIS - Medy Ompi (EKOTON, 2014)
Abalones release gametes in the water column, where eggs are fertilized. Fertilized eggs are develop into throchophore, veliger, and pediveliger larvae. Larvae will be in the water column up to three days, then it will go down into the sea bottom to settle, metamoprhose, and developed to be juvenile and adult of abalone. A penempelan is transition phase, where mortality rate is very hight. Larvae will search for suitable substrata, where larval behaviour, substrat quality, and current are important factors. Larval abalone will refuse to settle and swim back into water column, when substrata are not suitable. Substarta such as rock, dead coral, dead and branching coral, hard substrata covered by micro algae are favourable substrata for larva abalone to settle. Larvae of marine abalones have varying in swiming speed. These larvae can be trasported by current to a long the beach and also off shore. For abalone tropis H varia, the current speed less than 5 cm per second can stimulate larva Abalone tropis such as H varia to settle.